Laser-induced damages to charge coupled devices with combined nanosecond/picosecond short-pulse lasers - Cao, He; Xie, Xiaofan; Chang, Hao; Li, Yunfei; Yue, Jianfeng; Yu, Yu; Wang, Gong; Tang, Ziqi; Li, Lifang; Wang, Yulei; Lu, Zhiwei (Frontiers in Physics, 2024)
The research on laser induced breakdown mechanism of charge coupled devices (CCDs) brings new insights into photoelectric countermeasures. So far combined laser irradiation has been proved to be a more effective measure to destroy CCD. Due to the limitation of short-pulse laser combination method, the mechanism of CCD damage caused by combined short-pulse laser remains unexplored. Here, the distribution of temperature and stress field during the interaction between a combined short-pulse laser and a CCD is analyzed. A nanosecond/picosecond combined short-pulse laser system based on Stimulated Brillouin Scattering (SBS) pulse compression technique is designed. The damage threshold (DT) and properties of CCD by combined laser irradiation are characterized. The results show that the complete DT of combined laser induced CCD breakdown is only 103 mJ/cm 2 , which is only 44% of that of picosecond laser. The main cause of combined short-pulse laser induced CCD breakdown is short circuit (SC) between silicon substrate and silicon electrode.